The Gricean Cooperative Principle: Flouting And Hedging In The Conversations In Joseph Conradâs The Secret Agent - Sri Ningsih, M.G. (Jurnal Inspirasi, 2014)
The Cooperative Principle (CP) proposed by Grice states that a speaker should be cooperative by making the conversational contribution as required. In CP Grice proposes four conversational maxims : Quantity, Quality, Relation, andÂ Manner. Speakers sometimes flout the conversational maxims, so do characters in The Secret Agent. The flouting and hedging the conversational maxims can be done through figures of speech. Â Key words: the Gricean Cooperative Principle, flouting and hedging, figures of speech, conversations, The Secret Agent.